An Ex Vivo Study on Release, Uptake, and miRNA Profile of Exosomes in Rat Lens. (21st April 2022) - Zhang, Junfang; Luo, Jiawei; Zhang, Guowei; Qin, Bai; Ren, Xiumei; Guan, Huaijin
Abstract : Purpose . To identify the ability of releasing and uptaking exosomes in rat lens and characterize the exosomal microRNA profile of lens-derived exosomes. Methods . The rat lenses were cultured ex vivo and the medium was collected. The exosomes were isolated from medium and measured in size and concentration by nanoflow cytometry (nFCM) and transmission electron microscopy (TEM) and verified with CD63 and TSG101 by Western blot. The miRNAs in exosomes released from lens epithelial cells (LECs) were sequenced. The plasma exosomes labeled by PKH26 were used to verify the exosomes uptake LECs, and their colocalized fluorescence was imaged by confocal microscopy. Results . LECs released numerous exosomes into the medium through the capsule, which contained abundant miRNAs. The most abundant miRNAs included miR-184, let-7c-5p, let-7a-5p, let-7b-5p, let-7f-5p, miR-125a-5p, miR-204-5p, miR-125b-5p, miR-1b, and miR-23a-3p. The LECs but not the lens fibre cells showed exosome uptake. The LECs uptake more PKH26-labeled exosomes at day 7 than day 3 and day 14. Conclusions . Our results suggested that LECs can release and uptake exosomes through the capsule. Exosomes may be an important way for the lens to communicate among LECs, aqueous humour, vitreous body, and other ocular tissues.